PRAKTIK MANAJEMEN KEUANGAN MASJID BERBASIS PEMBERDAYAAN EKONOMI UMAT DI KOTA PURWOKERTO - Sochimin sochimin (IAIN Purwokerto, 2016)
Abstract: The mosque is one of the Muslims resources. Therefore, Muslims should utilize it optimally for their glory. Therefore, what Fatimatuzzahra mosque officials doing in the development of the mosque is a form of devotion to God and their efforts have already successfully used the mosque to be more productive and beneficial for the people. The results of the study, from 40 mosques sampled in this study, it appears that most of the mosques spent Rp 1.100.000, - s.d. Rp 2.500.000, -as many as 11 mosques, or 11%, while three mosques did not record average spending per month. Keywords: Mosque, Financial Management, Economic Empowerment.